Thyroid function before, during and after COVID-19 - Khoo,B; Tan,T; Clarke,S; Mills,E; Patel,B; Modi,M; Phylactou,M; Eng,PC; Thurston,L; Alexander,E; Meeran,K; Comninos,A; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: The effects of COVID-19 on the thyroid axis remain uncertain. Recent evidence has been conflicting, with both thyrotoxicosis and suppression of thyroid function reported. Objective: We aimed to detail the acute effects of COVID-19 on thyroid function and determine if these effects persisted upon recovery from COVID-19. Design: Cohort observational study. Participants and setting: Adult patients admitted to Imperial College Healthcare National Health Service Trust, London, UK with suspected COVID-19 between March 9 to April 22, 2020 were included, excluding those with pre-existing thyroid disease and those missing either free thyroxine (FT4) or TSH measurements. Of 456 patients, 334 had COVID-19 and 122 did not.Main Outcome Measures: TSH and FT4 measurements at admission, and where available, those taken in 2019 and at COVID-19 follow-up. Results: Most patients (86·6%) presenting with COVID-19 were euthyroid, with none presenting with overt thyrotoxicosis. Patients with COVID-19 had a lower admission TSH and FT4 compared to those without COVID-19. In the COVID-19 patients with matching baseline thyroid function tests from 2019 (n=185 for TSH and 104 for FT4), both TSH and FT4 were reduced at admission compared to baseline. In a complete cases analysis of COVID-19 patients with TSH measurements at follow-up, admission and baseline (n=55), TSH was seen to recover to baseline at follow-up. Conclusions: Most patients with COVID-19 present with euthyroidism. We observed mild reductions in TSH and FT4 in keeping with a non-thyroidal illness syndrome. Furthermore, in survivors of COVID-19, thyroid function tests at follow-up returned to baseline.